Determinants of Poverty In Indonesia - Nurul Azizah Az zakiyyah; Firsty Ramadhona Amalia Lubis; Intan Wahyuni Wahyuni (EKO-REGIONAL, 2023)
This study aims to determine the effect of economic growth, unemployment, labor, human development index (HDI), and the provincial minimum wage  on poverty in 34 provinces of Indonesia in 2018-2021. This study uses a quantitative approach method. The data used in this study is data from 34 provinces of Indonesia in 2018 – 2021. The analytical model used is a panel data regression analysis with a secondary Fixed Effect Model (FEM) approach.The results of the study with a significance level of 5% indicate that (1) simultaneously (together) the variables of economic growth, unemployment, labor, human development index, and the provincial minimum wage have a significant effect on poverty; (2) the economic growth variable has a positive and significant effect on poverty; (3) the unemployment variable has a positive and significant effect on poverty; (4) the labor variable has a negative and insignificant effect on poverty; (5) the human development index (HDI) variable has a negative and significant effect on poverty; (6) the variable of the provincial minimum wage has a negative and insignificant effect on poverty.